2015
DOI: 10.1167/iovs.15-17526
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Peeling-Induced Retinal Alterations on Intraoperative OCT in Vitreomacular Interface Disorders From the PIONEER Study

Abstract: PURPOSE. To assess retinal architectural alterations that occur following membrane peeling procedures and the impact of peel technique on these alterations utilizing intraoperative optical coherence tomography (iOCT).METHODS. This is a subanalysis of the prospective PIONEER iOCT study of eyes undergoing a membrane peeling for a vitreomacular interface (VMI) disorder. Intraoperative scanning was performed with a microscope-mounted OCT system. Macroarchitectural alterations (e.g., fullthickness retinal elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 23 publications
1
47
0
4
Order By: Relevance
“…[7,9,13,14,18,28,52,53] As such, iOCT can guide surgical decision-making during a membrane peeling case, including the identification of membrane that needs further peeling. Alternatively, it can signal the end of a case by confirming attainment of surgical goals.…”
Section: Clinical Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[7,9,13,14,18,28,52,53] As such, iOCT can guide surgical decision-making during a membrane peeling case, including the identification of membrane that needs further peeling. Alternatively, it can signal the end of a case by confirming attainment of surgical goals.…”
Section: Clinical Utilitymentioning
confidence: 99%
“…At the micro level of retinal architecture, some of the commonly reported changes following membrane peeling include expansion of the distance between the ellipsoid zone and the retinal pigment epithelium and alterations of the inner retinal surface. [11,18,52,53] The overall visual implications of the microarchitectural changes remain unclear. However, one study demonstrated that these intraoperative outer retinal alterations are directly correlated with rate of anatomic normalization following MH repair.…”
Section: Clinical Utilitymentioning
confidence: 99%
“…The 2-year PIONEER study [82] conducted in 2014 included 256 eyes, and the authors of the study reported that intraoperative HHOCT imaging impacted the surgeon's decision-making in 63 out of 146 procedures involving ERM peeling. A multitude of other findings stemmed from this study [177,178], including the demonstration of HHOCT for identifying persistent subretinal fluid [179] and HHOCT visualization of peeling-induced retinal alterations resulting from tissue manipulation with intraocular forceps and membrane scrapers [180]. Moreover, Binder et al [116] first demonstrated live 2D MIOCT imaging of human retinal surgery in between surgical steps and before/after surgery using a commercial Cirrus HD-OCT (Carl Zeiss Meditec; Oberkochen, Germany) adapted to the surgical microscope.…”
Section: Human Retinal Surgerymentioning
confidence: 84%
“…13,27 Both macroarchitectural and microarchitectural changes have been described in the retina following surgical manipulations. 46 In addition procedures where direct feedback has been documented includes subretinal perfluorocarbon liquid removal and subretinal injection of therapeutics. 35 In addition, more subtle changes occur in the outer retina with expansion of the EZ-RPE height following membrane peeling.…”
Section: Posterior Segmentmentioning
confidence: 99%